2014
DOI: 10.1097/shk.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Combined Zinc Supplementation With Proinsulin C-Peptide Treatment Decreases the Inflammatory Response and Mortality in Murine Polymicrobial Sepsis

Abstract: Zinc is a trace element vital for immune function during host response to infection. The proinsulin C-peptide has been shown to exert beneficial effects through activation of the anti-inflammatory peroxisome proliferator activated receptor-γ (PPARγ) in experimental endotoxemia. Some in vitro activities of C-peptide appear dependent upon the presence of zinc. We investigated the effect of zinc supplementation before onset of sepsis on the anti-inflammatory properties of C-peptide. Male C57BL/6 mice were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In a recent murine-model study, the addition of zinc to a C-peptide formulation reduced complications from sepsis. 26 Others have reported a significant decrease in C-peptide effects in the presence of EDTA; the authors of this study suggested that EDTA was probably binding calcium stores inside of the effected cells, therefore affecting Ca 2+ dependant Na + , K + , ATPase. 27 However, this is highly unlikely as EDTA would be in a charged state at physiological pH and would likely not cross a cell membrane and bind intracellular calcium stores.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In a recent murine-model study, the addition of zinc to a C-peptide formulation reduced complications from sepsis. 26 Others have reported a significant decrease in C-peptide effects in the presence of EDTA; the authors of this study suggested that EDTA was probably binding calcium stores inside of the effected cells, therefore affecting Ca 2+ dependant Na + , K + , ATPase. 27 However, this is highly unlikely as EDTA would be in a charged state at physiological pH and would likely not cross a cell membrane and bind intracellular calcium stores.…”
Section: Introductionmentioning
confidence: 63%
“…As a small example, one only needs to look at the number of reports in the literature identifying the importance of metals associated with C-peptide. 25,26 Interestingly, others have reported significantly reduced, or almost no biological activity, when C-peptide is in the presence of EDTA, a very strong zinc chelator that has the binding affinity to remove zinc from C-peptide and other zinc binding proteins such as albumin. 27 Moving forward, we suggest that all commercially or in-house synthesized C-peptide should be re-purified by HPLC and then characterized by mass spectrometry to ensure that the purity is as close to 100% as possible.…”
Section: Introductionmentioning
confidence: 99%
“…In a model of polymicrobial sepsis Zn deficiency resulted in increased NF-κB p65 mRNA expression and production in lungs resulting in up-regulation of target genes IL-1β, TNFα, and IcAM-1 (114), whereas Zn supplementation reduced neutrophil infiltration and MPO-mediated oxidative damage (115,116). Modulation of ERk1/2 and NF-κB pathways was shown to be critical for protective effect of zinc in lungs under septic conditions (117). correspondingly, patients with sepsis were characterized by low serum Zn levels that may occur due to increased ZIP8 (SLc39A8) mRNA expression.…”
Section: Zinc and Lung Inflammationmentioning
confidence: 99%
“…In a recent clinical trial, the supplementation of zinc (Zn) in infants aged between 7 and 120 days with probable serious bacterial infection resulted in significantly fewer treatment failures compared with placebo group (57). Such positive effects could be at least partially attributed to Zn-provoked inhibition of NF-.B in vital organs (58,59) and potentially to direct effects of Zn on some pathogens (60). It is worth mentioning that oral Zn supplementation given at high doses reduces morbidities (including sepsis-related) and mortality in preterm neonates (61).…”
Section: Promising Redox-active Agentsmentioning
confidence: 99%